Pola Komunikasi Coach Dengan Model Disabilitas Studi Pada Point Management Denpasar - Ratih Saputra, I Gusti Ayu Agung; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium, 2024)
As social beings, we cannot deny the necessity of communication. When communication is built on mutual understanding, openness, empathy, and trust among participants, it will be more successful. There are no borders that separate; rather, there is trust and understanding that communication is an information flow that is mutually beneficial. The aim of this study is to examine the patterns of communication between coaches and models who have disabilities. Studies on point management Denpasar. The data used in this study are primary data and secondary data, and data collection was carried out using interview techniques and documentation studies. The analysis technique used in this study is an interactive data analysis technique according to Miles and Huberman which consists of three strands, namely data reduction, data presentation and drawing conclusions. Based on the results of the test analysis it was found that there were three points of trainer communication with the model problem. These points consist of the way the trainer trains the model, the motivation given to the model and the wishes of the models.